Experimental investigation of the seismic performances of IMG reinforcement on curved masonry elements. (1st March 2015) - Giamundo, V.; Lignola, G.P.; Maddaloni, G.; Balsamo, A.; Prota, A.; Manfredi, G.
Abstract: In recent years, several new materials and technologies have been developed to limit the effects of earthquakes on the structures. In particular, for the structural reinforcement of masonry elements, the use of composite materials has shown to be effective. The experimental results of an innovative reinforcement technique based on inorganic matrixes, namely Inorganic Matrix composite Grid (IMG) are herein presented. The reinforcement has been applied to a full-scale masonry vault. Several shaking table tests (before and after the IMG reinforcement application) have been performed. The structural performance of the vault has been evaluated comparing the damages detected in the case of unreinforced and reinforced specimen.